396 Validate patent blue dye technique in sentinel lymph node for endometrial cancer staging in san borja arriaran hospital, chile. (18th September 2019) - Altamirano, R; Nazzal, O; Suarez, E
Abstract : Objectives: Validate patent blue dye technique in sentinel lymph node for endometrial cancer staging. Methods: We performed a prospective study (from 2014 to 2018) for endometrial cancer staging with patent blue dye sentinel lymph node before pelvic lymphadenectomy Blue dye injection was applied in the cervix (1cc 1cm deep and 1cc superficial) at 3 and 9 hour, 20 minutes prior starting surgery (laparotomy or laparoscopic). The sentinel lymph node was send to hematoxylin and eosin stain. Results: 60 surgeries were performed (75% laparoscopic and 25% laparotomy), and we were able to identified the a sentinel lymph node in 95% patients, 75% bilaterally, with an average of 1, 9 node. The most common site for identification was the obturador fossa, followed by external iliac artery. Only 3% of the nodes were identified in the para aortic region. We found 3% of the nodes in uncommon sites (abdominal pelvic wall), and 1 was cancer positive (with traditional lymphadenectomy negative to cancer). Our sensibility was 83% and specificity 95%. Conclusions: Even tough blue dye technique it's not the gold standard for sentinel lymph node staging, its sensibility and specificity allow us the use a less radical procedure with less operative time and complications. It is imperative that each surgeon and hospital team must perform their learning curve before adopting this technique.